Guaman Poma: From the Vision of the Vanquished to the Foundation of an Andean Lettered Discourse - García-Bedoya M., Carlos (2020)
Guaman Poma de Ayala has an excepcional place in the colonial Peruvian cultures. He is an indigenous intellectual and as the author of the Nueva corónica y buen gobierno, he is a member of the viceregal lettered city. He is an example of the full journey from ladino Indian to Andean intellectual. In this sense, he is also a foundational representation of the “migrant subject” as a counterpart of the “mestizo subject” that writes within the limits of the lettered canon and whose most famous example is Inca Garcilaso de la Vega. Guaman Poma positions himself as a hinge between early colonial Andean textualities subjected to transculturation. In this indigenous and mestizo discursive corpus, the denial of the European conquest has become a crucial thematic axis to present day. This essay departs from the author’s stories about the conquest to address the reasons and consequences of this denial.